Research Gate or Revolving Door? Uses and Gratifications of Academic Social Media Among Communication Scholars. (September 2021) - Cozma, Raluca; Dimitrova, Daniela
A survey of scholars in mass communication and related disciplines found that the academic social network ResearchGate is a popular platform for following like-minded academics, sharing one's work, locating relevant research, and managing one's academic reputation, in addition to gratifying more traditional social media needs, such as information seeking, social interaction, and even entertainment. The analysis revealed that academics who are extrinsically motivated to conduct research update their accounts more frequently but extract fewer benefits from the platform. Moreover, respondents agree that the RG Score generated by the social platform is not an accurate metric for one's research impact.